Pelatihan Pembuatan Briket Arang dari Hasil Pembakaran Sampah TPST di Desa Grogol Kecamatan Tulangan Kabupaten Sidoarjo - Diana Evawati (LPPM Universitas Yudharta Pasuruan, 2021)
Community participation in reducing the quantity or volume of waste as well as managing waste is an important component in tackling solid waste problems, especially in big cities. This training begins with socializing to the community the importance of waste management and the impact of waste on the surrounding environment. Furthermore, training was carried out on the process of making charcoal briquettes from the combustion of TPST, the use of charcoal briquettes as fuel and a source of UMKM in Grogol Village. The raw material for making charcoal briquettes is the result of burning waste in the TPST. Garbage will be burned at a temperature of 800 – 1000oC with a temperature that will be said to be complete combustion, the ash produced will be stable.